Heat-Mediated Activation of Affinity-Immobilized Taq DNA Polymerase. (April 1997) - Nilsson, J.; Bosnes, M.; Larsen, F.; Nygren, P.-Å.; Uhlén, M.; Lundeberg, J.
A novel strategy for heat-mediated activation of recombinant Taq DNA polymerase is described. A serum albumin binding protein tag is used to affinity-immobilize an E. coli -expressed Taq DNA polymerase fusion protein onto a solid support coated with human serum albumin (HSA). Analysis of heat-mediated elution showed that elevated temperatures (>70°C) were required to significantly release the fusion protein from the solid support. A primer-extension assay showed that immobilization of the fusion protein resulted in little or no extension product. In contrast, fusion protein released from the HSA ligand by heat showed high polymerase activity. Thus, a heat-mediated release and reactivation of the Taq DNA polymerase fusion protein from the solid support can be obtained to allow for hotstart PCR with improved amplification performance.